Os fundos de investimento imobiliário - Antunes, José Engrácia (2020)
This paper is addressed to the “real estate investment funds” (“fundos de investimento imobiliário”), aiming at analyzing its concept, legal nature and juridical regime, in particular the legal status of the fund’s management company.